A suggestion for the fusion of the two branches of the legal professions - Murphy, Joseph John (Statistical and Social Inquiry Society of Ireland, 1892)
It scarcely needs proof that the distinction between the two branches of the legal profession?between barrister and solicitor?is purely artificial, and incapable of justification on principles of ordinary common sense. There is in the nature of things no imaginable reason why the man who is competent to draw up a brief containing all that is important in a case, should be held incompetent to address the court and to examine the witnesses in the same case; and it is inevitable that such a distinction must often cause needless expense by requiring the employment of two men to do work which one man could do as well, and needless inconvenience by preventing the suitor from having direct verbal communication with the barrister who is to represent him before the judge, and conduct his case in court. I cannot add anything to what is familiar to most men on this subject; I take all this as granted, and go on with a suggestion as to the best way of getting rid of this anomaly and inconvenience.
Read Wednesday, 20th January, 1892
Keywords: Legal professions; Legal reform; 314.15